NOVEL PANGGIL AKU SAKAI: UPAYA PENGHEGEMONIAN YANG GAGAL - Yulita Fitriana (Madah: Jurnal Bahasa dan Sastra, 2012)
The novel Panggil Aku Sakai(PAS) describes the efforts of outsider to do hegemony, even to dominate the Sakai tribe. This research aims at revealing these efforts by using the hegemonical theory of Antonio Gramsci. This research finds that these hegemony has brought the suffering to Sakai people. They lose their forests where they live n also destroy their social and cultural life. Awareness of these things make the Sakai people to "fight" by isolating theirself from the outsider. It is making efforts hegemony failed.